Current directions in the prevention and treatment of Alzheimer’s disease - Hardy, John (Henry Stewart Talks, 2018)
Amyloid build-up and the importance of early diagnosis, The potential of inhibiting vs. clearing amyloid aggregation, Different potential therapeutic approaches designed for different stages of Alzheimer’s, The future of therapies targeting amyloid deposition